Flexible Multibody System Dynamics by Means of a Spectral Based Meshless Approach (Advances in Applied Mathematics and Mechanics, 2019)
It is a common practice in industry to model the elasticity in flexible multibody dynamics, when the deformations are small, by means of a linear finite element approach and of a model condensation strategy. Taking into account the flexibility in multibody modelling may require computationally expensive numerical models to be managed. Proper shape functions are introduced in this paper to model the displacements of flexible slender beam components, without the need of any spatial discretization; a novel formulation of the flexible properties of beam-like components follows and a small size motion equation set can be obtained. Modelling aspects, from point location to constraint equations and to elastodynamic modelling, are discussed. An ideal quick return mechanism, properly actuated, is modelled as a test case to prove the effectiveness of the proposed approach.